Successful Descemet Membrane Endothelial Keratoplasty in Proven Herpetic Endothelial Decompensation Requires Intensive Antiviral Therapy. Issue 2 (February 2020) - Friehmann, Asaf; Myerscough, James; Giannaccare, Giuseppe; Mazzoni, Maria; Bovone, Cristina; Busin, Massimo
Abstract : Purpose: To report the outcomes of Descemet membrane endothelial keratoplasty (DMEK) with intensive antiviral therapy for corneal edema secondary to herpes simplex virus type 1 (HSV-1)-mediated endotheliitis. Methods: All eyes with polymerase chain reaction positive for HSV-1 undergoing DMEK for endothelial decompensation between January 2014 and January 2018 were followed up prospectively at our tertiary referral center. All eyes had been free of active inflammation for a minimum of 9 months and were treated prophylactically with high-dose systemic and topical antivirals, which were continued for a prolonged period of time. Primary outcomes were the occurrence of immunological rejection and/or recurrence of endotheliitis, eventually resulting in graft failure. Secondary outcomes were best spectacle-corrected visual acuity and endothelial cell loss. Results: Four consecutive eyes of 4 patients were included with a mean (±SD) patient age of 68.5 ± 15.1 years. The postoperative follow-up averaged 22 months. No eyes exhibited any signs of immunologic rejection, recurrence of endotheliitis, or graft failure. Mean (±SD) decimal best spectacle-corrected visual acuity improved from 0.2 ± 0.1 to 0.7 ± 0.2 ( P = 0.007), whereas mean (±SD) endothelial cell loss was 56% ± 10.2% at the final postoperative follow-up. Conclusions: DMEK is an effective option to treat corneal edema secondary to HSV-1-related endotheliitis. Intensive antiviral prophylaxis may reduce the risk of recurrence and subsequent graft failure.